Ergonomic and efficiency analysis of conventional apple harvest process - Zhang, Zhao; Wang, Yuanjie; Zhang, Zhaohua; Li, Dapeng; Wu, Zhengze; Bai, Rui; Meng, Guangfu (International Journal of Agricultural and Biological Engineering, 2019)
Apples are still manually harvested by workers using ladders and buckets. Though it is known that manual apple harvest would probably lead to occupational injuries (e.g., back, neck, and shoulder strains), there has been little research that focuses on identifying the awkward activities/postures of pickers during the harvest process. After categorizing apple harvest work into 12 activities, this study used the method of Rapid Upper Limb Assessment (RULA) to identify awkward postures/activities that occurred during apple harvest. Awkward activities confirmed include descending a ladder, dumping apples, picking high and low apples on a ladder as well as on the ground, and moving a ladder, with potential reasons for each awkward activity provided. Meanwhile, it was demonstrated that pickers spent approximately 64% of working time under awkward postures that would lead to occupational diseases. In addition, this study analyzed picker harvest efficiency in terms of general and detail manners. The general mode assessed harvest activity in terms of picking and non-picking, with results showing that pickers averagely spent 76% (±7%) of harvest time in picking apples. Further analysis evaluated picking activities in terms of reaching, detaching, and transporting apples, with results showing that pickers spent averagely 30% (±6%) of time in detaching apples, which is the value time during apple harvest. Furthermore, valuable picking time ratio was obtained as the multiplication of picking time ratio and detaching time ratio. With a valuable ratio of 22% (±5%), it theoretically demonstrated the low harvest efficiency of the traditional harvest method. Since a majority of the awkward activities and the low efficiency were because of the ladders/buckets, using a harvest-assist unit may be a potential solution. Additionally, more efforts should be spent on the development of innovative mechanism to replace worker in placing attached apples to the bucket. Once the time for transporting apples is eliminated, the time for reaching apples is also removed, indicating the harvest efficiency would be improved significantly. Keywords: rapid upper limb assessment, awkward postures, apple harvest, safety, ergonomic analysis, harvest efficiency analysis DOI: 10.25165/j.ijabe.20191202.4567 Citation: Zhang Z, Wang Y J, Zhang Z H, Li D P, Wu Z Z, Bai R, et al. Ergonomic and efficiency analysis of conventional apple harvest process. Int J Agric & Biol Eng, 2019; 12(2): 210–217.